Mulheres lutando contra o HIV/SIDA: cuidadoras de Moçambique - Casimiro, Isabel Maria; Fauré, Yves-A; Tembe, Carlota Mondlane; Mutisse, Luisa Chicamisse (Desafios para Moçambique 2022, 2022)
Moçambique é um país caracterizado por índices elevados de pobreza onde a prevalência do Vírus da Imunodeficiência Humana (HIV)/Síndrome da Imunodeficiência Adquirida (SIDA) é muito alta e a taxa de incidência ainda preocupante, e cujos meios de combate à doença são limitados e dependem, em parte, da ajuda externa. A súbita emergência e rápida expansão da covid-19, a partir do início de 2020, teve um impacto negativo nas condições de tratamento das PVHIV, que, de certa forma, sofreram uma dupla aflição. Os serviços de saúde essenciais foram afectados - prevenção, diagnóstico, tratamento, cuidados paliativos e reabilitativos, etc. - com efeitos graves nos doentes mais vulneráveis (crianças, idosos, pessoas que vivem com doenças crónicas). Com este estudo, pretendemos apresentar os resultados obtidos através da divulgação das iniciativas das mulheres junto às autoridades públicas, instituições nacionais e internacionais, agências de cooperação bilaterais, associações e ONGs moçambicanas e estrangeiras dedicadas de uma ou de outra forma à luta contra o HIV/SIDA. Finalmente, almejamos examinar as condições em que estas iniciativas poderiam ser integradas ou pelo menos aproximadas das Unidades Sanitárias que trabalham na área do HIV/SIDA.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; gender / género; health / saúde; society / sociedade

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social